SUBSTITUTION FOR MACKEREL FISH (Scomberomorus commerson) BONE MEAL ON FISH CRACKERS - Bagus Hadiwinata; Putri Sri Wulandari; I Ketut Sumandiarsa; Rina Ardiyanti Ritonga; Toga Mahaji (Jurnal Perikanan Unram, 2024)
Fish bones are only considered waste by the community, even though they have good nutritional content, so they can be used as fish bone flour as an ingredient for fish crackers. To ensure the quality characteristics of fish crackers that have been substituted between fish bone flour and tapioca flour in fish crackers. Stages of the mackerel fish bone flour manufacturing process: preparation of raw materials for mackerel fish bones, boiling 1, washing, softening, boiling 2, baking, and flouring. Stages of the cracker processing process are: preparation of raw materials, washing fish, filleting, scraping meat, grinding, substitution of mixing fish bones and dough, forming, steaming, cooling, cutting, drying, baking, then frying. The results of the proximate analysis of fish bones showed water content of 5.77%, ash content of 60.20%, protein content of 11.26%, fat content of 2.58%, calcium content of 29.83%, ALT of 3.90x104 colonies/gram. The water content of the crackers produced ranged from 2.57% to 4.17%, the acid insoluble ash content of 0.05% to 0.41%, the protein content of 2.19% to 5.04%, the calcium content of 0.06% to 4.22%. The results of statistical analysis showed that there was an effect of mackerel fish bone flour substitution on water content, ash content, protein content, and calcium content. The Total Plate Count of crackers in all treatments obtained results <2.5x102 colonies/gram. The selected product in the P3 formulation with a calcium content of 4.22% increased the calcium content by 400%. The best sensory test of the formulation at P3 with 30 panelists on the parameters of appearance, odor, taste, and texture was still acceptable to the panelists.